On a thermoelastic laminated Timoshenko beam with delay term : well posedness and stability results - Kerbani, Ahmed Yacer; Choucha, Abdelbaki (Laghouat : Université Amar Telidji - Département de mathématiques, 2025)
In this work, we consider a thermoelastic Laminated Timoshenko beam with delay term, where the heat conduction is given by Cattaneo’s law. We establish the well posedness of the system. For stability results, we prove exponential decay of the system, especially in the case of equality in the hypothesis.